1964
DOI: 10.1002/jsfa.2740150907
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatographic examination of the fatty acids of coffee oil

Abstract: The fatty acids of the oil extracted from coffee have been examined by gas chromatography. The composition of the oil does not vary with the geographical origin of the coffee. Roasting of the coffee does not affect the composition of the oil. Coffee oil could be used for human consumption as a valuable source of essential fatty acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1967
1967
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 8 publications
1
9
0
1
Order By: Relevance
“…Ratnayake et al [33] also report a much higher concentration of lipids in espresso (2,260 mg/ L) than in metal screen-filtered coffee (335 mg/L) and drip-filtered coffee (13 mg/L). Other authors, for example, Jham et al [39], Martín et al [40] and Carisano and Gariboldi [41], found similar results for fatty acids in ground coffee concerning content and composition of fatty acids.…”
Section: Content Per Sip Of Coffeementioning
confidence: 56%
“…Ratnayake et al [33] also report a much higher concentration of lipids in espresso (2,260 mg/ L) than in metal screen-filtered coffee (335 mg/L) and drip-filtered coffee (13 mg/L). Other authors, for example, Jham et al [39], Martín et al [40] and Carisano and Gariboldi [41], found similar results for fatty acids in ground coffee concerning content and composition of fatty acids.…”
Section: Content Per Sip Of Coffeementioning
confidence: 56%
“…For some compounds, previous studies employing photo-ionisation mass spectrometry have been used to confirm the dominating compound [27]. Assignments in the text and the figures are due to the most abundant/likely compound for the respective nominal molecular mass (m/z) a Dominating structure confirmed by SPI-ITMS MS/MS measurements [27] constituents and their observed concentrations as well as on the physicochemical properties of the respective molecules (ionisation energies, photo-ionisation cross sections) the m/z values observed by PI-MS were assigned to chemical compounds [1,27,29,40,41]. For some molecular masses, SPI-MS/MS data [27] or wavelength specific SPI and REMPI photo-ionisation data [25,26] were additionally included.…”
Section: Spi Mass Spectrometry and Data Evaluationmentioning
confidence: 99%
“…The total fatty acid composition of coffee oil has been the subject of many investigations (Wurziger, 1963;Calzolari and Cerma, 1963;Carisano and Gariboldi, 1964;Hartmann et al, 1968;Pokorny and Forman, 1970;Streuli, 1970;Roffi et al, 1971;Chassevent et al, 1974;Vitzthum, 1976;Lercker et al, 1996). Folstar et al (1975) and Speer et al (1993) investigated the fatty acids in detail.…”
Section: Fatty Acidsmentioning
confidence: 99%
“…The presence of free fatty acids (FFA) in coffee has been described by various authors (Kaufmann and Hamsagar, 1962;Calzolari and Cerma, 1963;Carisano and Gariboldi, 1964;Wajda and Walczyk, 1978). All their data are expressed by the acid value, a common but indirect determination procedure used in the analysis of fat.…”
Section: Free Fatty Acidsmentioning
confidence: 99%